Exploring the relationship between teacher growth mindset, grit, mindfulness, and EFL teachers’ well-being - He, Jianyu; Iskhar, Shisir; Yang, Yan; Aisuluu, Moldobaeva (Frontiers in Psychology, 2023)
This study explores the relationship between teacher growth mindset, mindfulness, grit, and teacher well-being, with a particular focus on the mediating role of grit. The participants in this study were a number of 547 Chinese EFL teachers. Validated measures of growth mindset, mindfulness, grit, and occupational well-being were employed to collect data. Structural equation modeling was used to analyze the data and examine the hypothesized relationships. The findings indicate that both teacher growth mindset and teacher grit have a direct positive impact on teacher well-being. Furthermore, the results reveal that teacher grit serves as a mediator in the relationship between teacher mindfulness and teacher occupational well-being, suggesting that the positive effect of mindfulness on well-being is partially explained by the presence of grit. These findings contribute to our understanding of the factors influencing teacher well-being and emphasize the significance of fostering growth mindset, mindfulness, and grit in educational contexts. The implications of these findings for teacher training and support programs are discussed.